Isolation And Identification Of Yeasts From Butter Samples - Chhabra; Daljeet (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A Study was carried out to isolate and indentified yeast from butter samples procured from local market. Out of 30 butter samples, 29 isolates of yeast were recovered. Six different genera of yeast were identified from the samples under study. Out of total 29 isolates maximum 18 (62.06%) of genus Candida were found, followed by 4 (13.79%) of Rhodotorula, 3 (10.34 %) of Debaryomyces, 2 (6.89 %) of Kluyveromyces, and one each (3.44%) of genus Saccharomyces and Geotrichum.